Role of Cylindrospermopsis sp. in vertical nitrogen changes observed in tropical oxidation wastewater treatment ponds - M. Srichomphu; O. Phewnil; T. Pattamapitoon; Ratcha Chaichana; K. Chunkao; W. Wararam; N. Dampin; P. Maskulrath (Global Journal of Environmental Science and Management, 2024)
BACKGROUND AND OBJECTIVES: As a producer within the ecological food chain, phytoplankton provides the base energy and oxygen to the environment through photosynthesis and higher tropic levels. These benefits can be applied in five consecutive nature-by-nature oxidation ponds for the treatment of community wastewater coming through a high density polyethylene pipeline from the Phetchaburi Municipality located at the King’s Royally Initiated Laem Phak Bia Environmental Research and Development Project, Ban Laem District, Phetchaburi Province (Universal Transverse Mercator 47P 1442725 North 617774 East). This study focuses on the vertical distribution of the phytoplankton Cylindrospermopsis sp. and its relationship with nitrogen compounds in oxidation ponds.METHODS: Samples were collected from a community wastewater treatment system at various depths (30, 60, 90, 120, and 150 centimeters) below the water surface in April 2019 between 11:00 and 13:00 hours and analyzed for their chemical and physical properties. The analysis revealed a vertical relationship between Cylindrospermopsis sp. and wastewater. In the density of phytoplankton which were collected by measuring 20 liters of water and filtered using a 36-micron plankton net, calculated and counted under a high magnification microscope, as the species are classified according the taxonomy.FINDINGS: The results of the wastewater quality were as follows: the content of suspended solids was 65–81 milligram per liter, water temperature was 31.8–33.2°C, potential of hydrogen was 8.7–9.2, total nitrogen content was 4.0–5.3 milligram per liter, ammonium content was 0.03–0.06 milligram per liter, nitrate content was 0.09–0.12 milligram per liter, total phosphorus content was 0.9–1.3 milligram per liter, and phosphate content was 0.4–0.5 milligram per liter. In the density of phytoplankton, a significant correlation was observed between the population of Cylindrospermopsis sp. and water depth (R2 = 0.9324). The number of populations at the depths of 30, 60, 90, 120, and 150 centimeters were 3.2 × 107, 1.6 × 107, 1.1 × 107, 5.5 × 107, and 1.1 × 108 cells per cubic meter, respectively.CONCLUSION: The different densities of Cylindrospermopsis sp. found at different depths throughout the treatment pond are related to the nitrogen dynamics of the water body. The results of this study revealed that organic nitrogen, including ammonium, was assimilated and converted to inorganic nutrients, which promoted the growth of other phytoplankton species. The correlation between Cylindrospermopsis sp. and total nitrogen and ammonium showed significance at R2 = 0.7268 and 0.797, respectively, with a confidence level of 0.05. Therefore, to ensure treatment effectiveness, the depth of wastewater treatment ponds should be considered during their construction because phytoplankton regulation plays an important role to maintain the overall treatment efficiency.